The development of diesel oxidation catalysts and the effect of sulfur dioxide on catalysts of metal-based diesel oxidation catalysts: A review - Zhang, Zhiqing; Tian, Jie; Li, Jiangtao; Cao, Chao; Wang, Su; Lv, Junshuai; Zheng, Wenling; Tan, Dongli (Fuel processing technology, 2022)
With the rapid development of industry, the diesel engine as a power source has brought many benefits in promoting economic growth and industrial automation. However, the diesel engine cannot underestimate the harm to air pollution and human health. Therefore, the requirements for the improvement of diesel engine emission standards are higher and higher. Since the introduction of emission regulations to limit the emission of harmful emissions from diesel engines to the environment, the diesel oxidation catalyst (DOC) has been an essential part of the diesel exhaust system. The DOC is one of the most significant catalysts for diesel engine aftertreatment catalysts. Its primary function is to oxidize unburned hydrocarbon (HC) and carbon monoxide (CO) produced in the combustion process into harmless water (H2O) and carbon dioxide (CO2). At the same time, it can also convert nitric oxide (NO) in engine exhaust into nitrogen dioxide (NO2) for passive regeneration of downstream diesel particulate filter (DPF) and improve the nitrogen oxide (NOx) conversion efficiency of selective catalytic reduction (SCR). This review covers the status, preparation methods, the influence and measures of sulfur dioxide (SO2) on catalysts, and the methods of developing anti-SO2 catalysts in the future of DOC. Firstly, the working principle and composition of DOC were discussed. Secondly, the preparation method and process of DOC were introduced. Thirdly, the development trend of DOC was analyzed. Then this paper focused on the impact of SO2 on DOC and the measures to alleviate SO2 poisoning. Finally, the possible methods of anti-SO2 DOC design in the future were prospected. The work in this paper can effectively promote the application of DOC. Based on the work done in this paper, the researchers can efficiently select appropriate DOC according to the future research situation. [Display omitted] •Processes of preparation method and develop are listed.•Optimization applications in diesel engine are investigated.•The future trend of anti SO2 catalysts is discussed.•Improvement suggestions for performance enhancement of diesel oxidation catalysts are proposed.